Kesadaran Gender sebagai Regulasi Psikologis: Tinjauan Literatur tentang Perubahan Pola Pikir pada Laki-laki dan Perempuan - Danny Khoyana Djulijanto; Lauw Acep; Edi Priyono (JURNAL ILMIAH NUSANTARA, 2026)
This study aims to explore the role of gender awareness as a psychological regulatory mechanism underpinning shifts in the mindset of men and women. Amid shifting global social norms, gender awareness is no longer viewed merely as cognitive knowledge, but rather as an active process of self-regulation. Through a systematic literature review of 27 scientific articles from the SINTA, Scopus, and Google Scholar databases, this study analyzes how a deep understanding of the social construction of gender functions as a self-control tool that enables individuals to monitor, evaluate, and adjust their behavior. Findings indicate that gender awareness triggers a shift from a fixed mindset rooted in biological essentialism toward an adaptive growth mindset. In men, this change is reflected in the redefinition of inclusive masculinity (anti-toxic masculinity), while in women, it manifests as increased self-efficacy and agency. This article concludes that strengthening gender awareness is an essential strategic psychological intervention for achieving sustainable gender equality at both the individual and structural levels.